2012
DOI: 10.1371/journal.pone.0034646
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Endostatin Normalizes Tumor Vasculature and Enhances Radiation Response in Xenografted Human Nasopharyngeal Carcinoma Models

Abstract: BackgroundHypoxic tumor cells can reduce the efficacy of radiation. Antiangiogenic therapy may transiently “normalize” the tumor vasculature to make it more efficient for oxygen delivery. The aim of this study is to investigate whether the recombinant human endostatin (endostar) can create a “vascular normalization window” to alleviate hypoxia and enhance the inhibitory effects of radiation therapy in human nasopharyngeal carcinoma (NPC) in mice.Methodology/Principal FindingsTransient changes in morphology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 41 publications
(57 reference statements)
6
60
0
Order By: Relevance
“…Xianlu Zhuo et al assessed Microvessel density (MVD) in 65 cases of clinical paraffin-embedded NPC tissues, and found that MVD was closely related to NPC progression as reflected by distant metastasis (P < 0.05) [8]. Fang Peng et al have found that anti-angiogenesis could normalize NPC vasculature and enhance radiation response [27]. Therefore, some mechanistic insights into angiogenesis are emerging.…”
Section: Discussionmentioning
confidence: 99%
“…Xianlu Zhuo et al assessed Microvessel density (MVD) in 65 cases of clinical paraffin-embedded NPC tissues, and found that MVD was closely related to NPC progression as reflected by distant metastasis (P < 0.05) [8]. Fang Peng et al have found that anti-angiogenesis could normalize NPC vasculature and enhance radiation response [27]. Therefore, some mechanistic insights into angiogenesis are emerging.…”
Section: Discussionmentioning
confidence: 99%
“…The paracrine/autocrine role of vascular endothelial growth factor (VEGF) by binding to its receptors is one important component of tumor microenvironment and its self regulation. Suppression of VEGF gene expression could enhance the radiosensitivity of cancer cells [4], [5]. And VEGFR2 is usually considered to mediate the main function attributed to VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…During vascular normalization, treatment with paclitaxel was identified to exhibit a maximal effect on tumor growth inhibition (38). In addition, Endostar was demonstrated to normalize tumor vasculature, which alleviated hypoxia and significantly sensitized the antitumor function of radiation in human nasopharyngeal cancer (39). Based on energy metabolism, the present study investigated the underlying mechanism through which Endostar exhibits a radiosensitization effect.…”
Section: Discussionmentioning
confidence: 95%